Strategic management accounting practices and value creation: towards good governance and accountability in government linked companies - Nik Abdullah, Nik Herda; Said, Jamaliah (2016)
Government Linked Companies serve as the backbone of Malaysia’s economy by contributing to 35 percent of the Gross Domestic Product (GDP) and employing more than 270,000 employees.By definition, Government Linked Companies are government business entities that are privatized and are major shareholders as well as provide services deemed as a social responsibility to the public.As such, Government Linked Companies need to demonstrate good governance and a high level of accountability in order to achieve these objectives. This research paper aims at examine the relationship between strategic management accounting practices and value creation in the context of Malaysian Government Linked Companies. Based on questionnaires from 125 respondents drawn from Government Linked Companies, the findings showed a significant positive relationship between strategic management accounting practices and value creation. Thus, certain types of strategic management techniques have become the focus of a majority of the research carried out.Nevertheless, one important element, which is the relationship between strategic management accounting practices and value creation, has not been studied much. The company’s top management and management accountants have been urged to re-evaluate the emerging role of strategic management accounting in establishing firm value based on the practical guidance provided by this study. Moreover, this paper has enriched the pertinent literature and provided an assessment of strategic management accounting and value creation for researchers and practitioners.